PENGARUH SELF REGULATED LEARNING DAN KECEMASAN MATEMATIS TERHADAP HASIL BELAJAR MATEMATIKA SISWA SMP LESTARI BERINGIN - Putri Septi Isnaini; Nurdalilah NurDalilah (Universitas Asahan, 2023)
This study has the objectives: (1) to find out whether there is an effect of self-regulated learning on students' mathematics learning outcomes, (2) to find out whether there is an effect of mathematical anxiety on students' mathematics learning outcomes, (3) to find out whether self-regulated learning and anxiety mathematics together influence the results of student mathematics learning. This research is a quantitative research, the population in this research is class VII students of SMP Lestari Beringin, academic year 2022/2023. The sample used in this study were all students of class VII, totaling 50 students. Based on the results of data processing, it was found that the significance value for self-regulated learning was 0.393 > 0.05 and the significance value for mathematical anxiety was 0.988 > 0.05. This means that partially self-regulated learning factors and mathematical anxiety affect students' mathematics learning outcomes. Meanwhile, based on the multiple regression analysis test, the Fcount value was 0.371 with a significance value of 0.692 > 0.05 so that there was a significant influence between self-regulated learning and mathematical anxiety together on learning outcomes in mathematics. An R2 value of 0.26 was obtained, meaning that 26% of the change in students' mathematics learning outcomes together with self-regulated learning and mathematical anxiety, while the rest was explained by various other variables not analyzed in this study.Keywords: Self regulated learning, mathematical anxiety, learning outcomes of mathematics